Integrated Solutions for Sustainable Growth: Merging Inflation Control, Food Security, and Digitalization in Sumatra Indonesia - Piliang, Arfah; Winardo, Tommy; Zubir, Zubir; Jonnedi, Jonnedi (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study examines the impact of inflation control, food security, and digitalization on regional economic stability in Sumatra, Indonesia. Using Structural Equation Modeling (SEM)-PLS, this study analyzes the direct and indirect relationship between inflation control policies, food security, the downstream supply chain, fiscal policy, regional investment, and digital transformation. In addition, this study introduces real sector innovation and institutional capacity as mediating variables to explain how these policies affect economic stability. The results showed that the overall hypothesis proved to be significant (p < 0.05), with the coefficient of influence of inflation control of 0.45 (t-value 5.42), food security of 0.38 (t-value 4.18), food downstream of 0.31 (t-value 3.91), fiscal policy of 0.42 (t-value 4.98), regional investment of 0.36 (t-value 4.21), and digitalization of the economy of 0.33 (t-value 4.05). The results show that well-coordinated policy synergy, integrating inflation control, food security enhancement, and digitalization, significantly reduces inflation and increases regional economic stability. Real-sector innovation plays a vital role in mediating the relationship between food security and financial stability, while institutional capacity is proving critical to the effectiveness of fiscal policy implementation. Sumatra's local governments must accelerate digital transformation and food security policies, increase real-sector innovation, and strengthen institutional capacity to drive sustainable economic growth.